Infection fatality ratio and case fatality ratio of COVID-19. (December 2021) - Luo, Guangze; Zhang, Xingyue; Zheng, Hua; He, Daihai
Highlights: The infection fatality ratio (IFR) of COVID-19 is the risk of death per infection. IFR is estimated based on reported deaths and serologically inferred infections. RT-PCR-confirmed deaths were much lower than the excess deaths in some countries. RT-PCR-based case fatality rate under extensive testing is a reliable proxy of IFR. Abstract: The infection fatality ratio (IFR) is the risk of death per infection and is one of the most important epidemiological parameters. Enormous efforts have been undertaken to estimate the IFR for COVID-19. This study examined the pros and cons of several approaches. It is found that the frequently used approaches using serological survey results as the denominator and the number of confirmed deaths as the numerator underestimated the true IFR. The most typical examples are South Africa and Peru (before official correction), where the confirmed deaths are one-third of the excess deaths. We argue that the RT-PCR-based case fatality ratio (CFR) is a reliable indicator of the lethality of COVID-19 in locations where testing is extensive. An accurate IFR is crucial for policymaking and public-risk perception.